Meta-analysis of heritability estimates and genome-wide association for tick-borne haemoparasites in African cattle - Riggio, Valentina; Madder, Maxime; Labuschagne, Michel; Callaby, Rebecca; Zhao, Rongrong; Djikeng, Appolinaire; Fourie, Josephus; Prendergast, James G. D.; Morrison, Liam J. (Frontiers in Genetics, 2023)
The control of tick-borne haemoparasites in cattle largely relies on the use of acaricide drugs against the tick vectors, with some vaccination also being used against selected pathogens. These interventions can be difficult in Africa, where accessibility and cost of vaccines can be issues, and increasing resistance of the tick vectors to the widely used acaricides is complicating disease control. A potential complementary control strategy could be the exploitation of any natural host genetic resistance to the pathogens. However, there are currently very few estimates of the extent of host resistance to tick-borne haemoparasites, and a significant contributing factor to this knowledge gap is likely to be the difficulty of collecting appropriate samples and data in the smallholder systems that predominate livestock production in low- and middle-income countries, particularly at scale. In this study we have estimated the heritability for presence/absence of several important haemoparasite species (including Anaplasma marginale, Babesia bigemina, Babesia bovis and Ehrlichia ruminantium), as well as for relevant traits such as body weight and body condition score (BCS), in 1,694 cattle from four African countries (Burkina Faso, Ghana, Nigeria and Tanzania). Heritability estimates within country were mostly not significant, ranging from 0.05 to 0.84 across traits and countries, with standard errors between 0.07 and 0.91. However, the weighted mean of heritability estimates were moderate and significant for body weight and BCS (0.40 and 0.49, respectively), with significant heritabilities also observed for the presence of A. marginale (0.16) and E. ruminantium (0.19). In meta-analysis genome-wide association studies for these traits, two peaks were identified as reaching the suggestive significance threshold (P < 1.91 x10-7 and P < 1.89 x10-7, respectively). One on chromosome 24 for BCS and one on chromosome 8 for E. ruminantium infection status. These findings indicate that there is likely to be a genetic basis that contributes to pathogen presence/absence for tick-borne haemoparasite species, which could potentially be exploited to improve cattle resistance in Africa to the economically important diseases caused by these pathogens.